Experiências de mulheres no pós parto em situação de vulnerabilidade usuárias de implante de etonogestrel - Taliassaqui, Raquel Gonçalves dos Santos (Universidade Federal de São Carlos, 2025)
In Brazil, many unplanned pregnancies occur during the postpartum period, causing harmful consequences for women, children, and families. The use of an appropriate contraceptive method in this group aims to mitigate this unfavorable situation. In this sense, long-acting contraceptive methods (LARC) appear to be quite satisfactory options due to their specific characteristics, especially the etonogestrel subdermal implant. This study aims to evaluate the experiences of vulnerable postpartum women using the etonogestrel implant in a city in the interior of the state of São Paulo. The study has an observational, cross-sectional, descriptive/quantitative profile of postpartum women who have been using this method for at least three months. The survey revealed that the social profile of most participants was between 17 and 19 years old (24.1%), mixed race (41.4%), high school graduates (31%), and the majority were single (51.7%), and evangelical (27.6%). Regarding parity, the vast majority of women already had at least one child (93.1%). Regarding vulnerability, the most common conditions were alcohol and/or drug use (28%), adolescents with children (24%), and mental and cognitive disorders (20%). Regarding previous contraceptive methods, we found that more than half of the women were already using some form of contraception before implants (51.7%), with the main choices being oral contraceptives and male condoms. Breastfeeding was also common among study participants (82.7%), with the duration ranging from 1 month to 2 years and 4 months. The implant was considered satisfactory by most participants (55.2%), with efficacy (65.5%) and convenience (34.4%) being the main positive aspects reported. Regarding bleeding patterns, 41.3% reported patterns considered favorable (infrequent/regular/amenorrhea). Although frequent and prolonged bleeding was the main complaint (55.1%), and prolonged bleeding predominated between 6 and 24 months, with a tendency to improve after this period, 75% of users were satisfied with their bleeding pattern, and almost half (48.2%) considered the reduction in menstrual flow positive. The data obtained allow us to conclude that there is a trend toward a high level of overall satisfaction among users of the etonogestrel implant, reinforcing its efficacy, convenience, and suitability, especially in vulnerable settings.
Experiences of postpartum women in vulnerable situations using etonogestrel implant
Keywords: Experiência de vida; Vulnerabilidade em saúde; Período pós-parto; Implante de etonogestrel; Life experience; Health vulnerability; Postpartum period; Etonogestrel implant.; CIENCIAS DA SAUDE::MEDICINA; 3. Saúde e Bem-Estar